EFFECT OF COOKING ON IRON AVAILIBILITY IN FORTIFIED HOMEMADE TEMPEH - Micha Mahardika; Fauzan Amin; Arda Ganda Risdiyono (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Iron deficiency anemia is a type of anemia caused by iron deficiency, decreasing in the number of healthy red blood cells. The purpose of this study was to make fortified Fe-EDTA and find out the changes in iron availability after cooking (frying and boiling). The biological availability test for iron was carried out in vitro by simulating human digestion using enzyme pepsin and pancreatin-bile solution. The iron variants added were 0, 0.033, 0.066, 0.099, 0.132, and 0.166 % of EDTA iron on 30 grams of raw soybeans to be homemade tempeh. Test results with Atomic Absorption Spectrometry (AAS) showed that the highest Fe content of 12.54 mg was obtained by adding 0.166% of EDTA iron to raw tempeh. But after cooking, there is a decrease in fried and boiled tempeh. The results obtained from the addition of 0.166% of iron-EDTA are 7.74 mg for fried tempeh, and 8.40 mg for boiled tempeh. The results of the addition of Fe-EDTA 0.166% for raw tempeh and boiled match to the value of daily Fe intake to reduce iron anemia in the amount of 8-15 mg / day according to Recommendation Dietary Allowance (RDA). The addition of 0.166% of Fe-EDTA fortification on dried tempeh, it still has not match to the recommended level.Received: 13 September 2019; Accepted: 30 December 2019; Published: 12 January 2020